Oral manifestations resulting from chemotherapy treatment in children and adolescents: An integrative review (Research, Society and Development, 2023)
Objective: This integrative review aimed to evaluate the main oral changes resulting from chemotherapy among children and adolescents, regarding country, design, duration, sample, sex, age and place where it was carried out. Materials and methods: The bibliographic survey was carried out through online access to VHL Brasil (Virtual Health Library) and Pubmed (Medical literature Analysis and Retrieval System on-line). For the search, the following descriptors were used:  “Oral Manifestations”, “Drug Therapy”, “Child”, “Adolescent”. The MEDLINE, LILACS, BBO and PUBMED databases were used in Portuguese, English and Spanish between the years 2002 and 2022. Most studies were carried out in Brazil, followed by Mexico and Ukraine. The sample ranged from 23 (twenty-three) to 103 (one hundred and three) patients and its duration varied from 02 (two) to 86 (eighty-six) months. Results: The main oral manifestations found were: Mucositis with a prevalence of 14.2% to 98%; Fungal infections 8.9% to 78%; Hyposalivation 7.4% to 100% and Ulcer 15% to 100%. Conclusion: The conclusion of this integrative review shows a high occurrence of oral manifestations in pediatric patients undergoing chemotherapy. These oral manifestations can be avoided or minimized through the insertion of the dentist as an integral part of patient care, providing their well-being.